Measures to ensure the integrity of existing buildings and structures and monitoring the impact of new building on environmental conditions under conditions - Hryhorovskyi, P.; Oryshchenko, V.; Tugay, A. (Ways to Improve Construction Efficiency, 2021)
The practice of construction in the conditions of compacted urban development shows that the construction work is likely to lead to a number of dangerous events, which are caused by additional loads on the structures of nearby facilities. The probability, nature, rate of development of undesirable processes and the degree of their danger depends on many factors that will be discussed in the article. Each building, structure or individual structure has a functional purpose, is operated under certain conditions and must meet safety requirements, ie the requirements of preventing accidents and collapses of the building as a whole or its components that may pose a danger to health and human life, or harm the environment and cause other emergencies. Significant experience has been gained in the reliability of buildings and structures in terms of determining the indicators of reliable and trouble-free operation of construction sites under normal operating conditions, ie work in the design mode. However, the vast majority of facilities in real operating conditions under the influence of various unforeseen and uncertain factors of influence, changing the design boundary conditions creates a direct risk of destruction. Monitoring is one of the main ways to prevent and make the necessary decisions in a timely manner to ensure the integrity of buildings and structures in compacted buildings in cases where new construction has a negative impact on these facilities. According to the research results, it is established that the main factors that determine the compacted conditions in the area of the pit and earthworks are the distance from the pit to the adjacent buildings and roads; soil base properties; the depth of the pit. The main reasons for the deformation of existing buildings during the new construction next to them, which is primarily the installation of ditches, is the increase in stresses in the base under the foundations of the surrounding buildings. The foundations of buildings work together with the soil base, and the development of their excessive deformations, uneven sediments and rolls leads to the destruction or further reduction of the serviceability of the responsible structural elements of the facilities in operation. The article presents the main compensatory measures for the protection of adjacent buildings during new construction.